The implementation of electrical energy conservation in industrial and commercial buildings / Beny Yusmar - Yusmar, Beny (2009)
Electricity conservation is one method of energy savings besides using efficient electrical appliances, while enjoying the same level of functions and services. Electrical can be conserved through several ways. It can be conserved by the consumers themselves and also through the use of appliances that provide the conservation of electricity technologies. As such, by conserving energy in buildings and for building, it can contribute towards sustainability the environment. This study enquiry regards that the implementation of electrical energy conservation system in industrial and commercial buildings has been well below par. Only few buildings are implementing the system to reduce their operational cost. This study has defined two types of the electrical energy conservation system that have been used; namely electrical device implementation and building design with electrical device implementation. This study also establishes that lighting system and air-conditioning system contribute to the electrical wastage in case study buildings. This study also reveals that the production and office areas are using the electrical energy conservation system the most.